Olfactory‐cognitive index distinguishes involvement of frontal lobe shrinkage, as in sarcopenia from shrinkage of medial temporal areas, and global brain, as in Kihon Checklist frailty/dependence, in older adults with progression of normal cognition to Alzheimer's disease. Issue 3 (19th January 2021) - Iritani, Osamu; Okuno, Tazuo; Miwa, Takaki; Makizako, Hyuma; Okutani, Fumino; Kashibayashi, Tetsuo; Suzuki, Kumiko; Hara, Hideo; Mori, Eri; Omoto, Shusaku; Suzuki, Hirokazu; Shibata, Minori; et al.
Abstract : Aim: Olfactory impairment as a prodromal symptom, as well as sarcopenia, frailty and dependence as geriatric syndromes, is often associated with cognitive decline in older adults with progression of Alzheimer's disease. The present study aimed to evaluate the associations of olfactory and cognitive decline with these geriatric syndromes, and with structural changes of the brain in older adults. Methods: The participants were 135 older adults (47 men and 88 women, mean age 79.5 years), consisting of 64 with normal cognition, 23 with mild cognitive impairment and 48 with Alzheimer's disease. Olfactory function was evaluated by the Open Essence odor identification test. Shrinkage of the regional brain was determined by magnetic resonance imaging. Results: Logistic regression analysis with Open Essence, Mini‐Mental State Examination, age and sex as covariates showed higher olfactory‐cognitive index (|coefficient for Open Essence (a) / coefficient for Mini‐Mental State Examination (b)|) in participants with sarcopenia (Asia Working Group for Sarcopenia), and lower values of (|a/b|) in participants with Barthel Index dependence, Kihon Checklist frailty, Lawton Index dependence and support/care‐need certification as objective variables. Logistic regression analysis adjusted by age and sex also showed significant shrinkage of the frontal lobe in participants with AWGS sarcopenia, especially in women, and shrinkage of the medial temporal areas and global brain in participants with Kihon Checklist frailty/dependence. Conclusions: Olfactory‐cognitive index (|a/b|) might be a useful tool to distinguish involvement of frontal lobe shrinkage, as in sarcopenia from shrinkage of the medial temporal areas, and global brain, as in frailty/dependence, in older adults with progression of normal cognition to Alzheimer's disease. Geriatr Gerontol Int 2021; : – .